Emerging molecular techniques for studying microbial community composition and function in microbiologically influenced corrosion. (October 2019) - Kotu, Susmitha Purnima; Mannan, M. Sam; Jayaraman, Arul
Abstract: Microbiologically influenced corrosion (MIC) accounts for approximately 20–50% of total corrosion costs in the United States. Microorganisms causing MIC in various field locations such as oil pipelines and cooling water systems have been historically studied using either culture- or DNA hybridization- or polymerase chain reaction (PCR)-based methods to estimate levels of the microorganisms (e.g., sulfate reducing bacteria) present in the community and obtain an accurate microbial fingerprint of the community. While these approaches provide information on the community composition at each MIC-impacted field location, the composition of microbial communities is distinct at different MIC impacted field locations and equipment. Moreover, all the microorganisms identified at a specific MIC impacted location need not contribute to the observed corrosion at that location. Since metabolism gives a direct readout of microbial activity, an emerging hypothesis is that correlating the metabolic footprint of the community to the microbial community composition can provide information on the key microbial species involved in MIC. This review discusses advances in molecular methods for investigating microbial community composition and metabolic footprint that are needed, along with information on electrochemical mechanisms, to develop a comprehensive understanding of MIC mechanisms. Highlights: Investigating microbial communities is vital for systems-level understanding of MIC. Use of metabolomics methods for investigating microbial communities is recently emerging. Metabolomics methods provide insights to the formation of microbial communities and initiation of MIC. Composition and function are equally important to characterize a microbial community. Integrating –omics data with current knowledge on MIC mechanisms is critical for comprehensive knowledge of MIC.